Seasonal Changes in Pinus tabuliformis Root-Associated Fungal Microbiota Drive N and P Cycling in Terrestrial Ecosystem - Wang, Hai-Hua; Chu, Hong-Long; Dou, Qing; Feng, Huan; Tang, Ming; Zhang, Shuo-Xin; Wang, Chun-Yan (Frontiers in Microbiology, 2021)
In terrestrial ecosystems, mycorrhizal roots play a key role in the cycling of soil carbon (C) and other nutrients. The impact of environmental factors on the mycorrhizal fungal community has been well studied; however, the seasonal variations in the root-associated fungal microbiota affected by environmental changes are less clear. To improve the understanding of how environmental factors shape the fungal microbiota in mycorrhizal roots, seasonal changes in Pinus tabuliformis root-associated fungi were investigated. In the present study, the seasonal dynamics of edaphic properties, soil enzymatic activities, root fungal colonization rates, and root-associated fungal microbiota in P. tabuliformis forests were studied across four seasons during a whole year to reveal their correlations with environmental changes. The results indicate that the soil functions, such as the enzymatic activities related to nitrogen (N) and phosphorus (P) degradation, were varied with the seasonal changes in microclimate factors, resulted in a significant fluctuation of edaphic properties. In addition, the ectomycorrhizal fungal colonization rate in the host pine tree roots increased during warm seasons (summer and autumn), while the fungal colonization rate of dark septate endophyte was declined. Moreover, the present study indicates that the fungal biomass increased in both the pine roots and rhizospheric soils during warm seasons, while the fungal species richness and diversity decreased. While the Basidiomycota and Ascomycota were the two dominant phyla in both root and soil fungal communities, the higher relative abundance of Basidiomycota taxa presented in warm seasons. As well, the fungal microbial network complexity declined under the higher temperature and humidity conditions. The present study illustrates that the varieties in connectivity between the microbial networks and in functional taxa of root-associated fungal microbiota significantly influence the soil ecosystem functions, especially the N and P cycling.